Helicobacter pylori Eradication Therapy Affect the Gut Microbiota and Ghrelin Levels - Martín-Núñez, Gracia Mª; Cornejo-Pareja, Isabel; Clemente-Postigo, Mercedes; Tinahones, Francisco J.; Moreno-Indias, Isabel (Frontiers in Medicine, 2021)
Background: Antibiotic therapy used to eradicate Helicobacter pylori has been associated with changes in plasma ghrelin and alterations in the gut microbiota. On the other hand, changes in ghrelin levels have been related to changes in gut microbiota composition. Our aim was to evaluate the relationship between changes in the gut microbiota and ghrelin levels in H. pylori infected patients who received antibiotic treatment for its eradication. Methods: A prospective case-control study that included fourty H. pylori-positive patients who received eradication therapy (omeprazole, clarithromycin, and amoxicillin) and twenty healthy H. pylori antigen-negative participants. Patients were evaluated before and two months after treatment. Gut microbiota composition was analyzed through 16S rRNA amplicon sequencing (IlluminaMiSeq). Results: H. pylori eradication treatment decreased ghrelin levels and caused changes in gut microbiota profiles. Gut bacteria such as Bifidobacterium longum, Bacteroides, Prevotella, Parabacteroides distasonis and RS045 have been linked to ghrelin fasting and / or post-meals. Changes in the abundance of Lachnospiraceae, its genus Blautia, as well as Prevotella stercorea, and Megasphaera have been inversely associated with changes in ghrelin after eradication treatment. Conclusions: Erradication treatment for H. pylori produces changes in the composition of the intestinal microbiota and ghrelin levels. The imbalance between lactate producers such as Blautia, and lactate consumers such as Megasphaera, Lachnospiraceae or Prevotella, could trigger changes related to ghrelin levels under the alteration of the antibiotic H. pylori. In addition, acetate producing bacteria such as B. longum, Bacteroides, and Parabacteroides distasonis could also play an important role in ghrelin regulation.